2009
DOI: 10.1088/0022-3727/42/21/215102
|View full text |Cite
|
Sign up to set email alerts
|

Silver–silver oxide core–shell nanoparticles by femtosecond laser ablation: core and shell sizing by extinction spectroscopy

Abstract: The generation of small silver metal nanoparticles (Nps) by ultrashort pulsed laser ablation has been an active area of research in recent years due to their interest in several fields of applied research such as biotechnology and material research, in particular those with sizes smaller than 10 nm. In general, laser ablation tends to produce environmentally clean metal Nps compared with wet chemical methods. However, since silver may be oxidized in the presence of water or ethanol, core–shell silver–silver ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 21 publications
1
36
0
5
Order By: Relevance
“…In case of Ag NP, the predicted surface coverage of 137 % Ag + exceeds monolayer coverage while the cited experimental study found a significantly lower amount of oxidation (~80 % Ag + ). Note that other experimental studies from Schinca et al [142] as well as Giorgetti et al [143] both report on the generation of Ag/Ag 2 O core-shell NPs based on extinction spectroscopy and application of Mie theory modeling.…”
Section: Surface Oxidization[b] [%]mentioning
confidence: 99%
“…In case of Ag NP, the predicted surface coverage of 137 % Ag + exceeds monolayer coverage while the cited experimental study found a significantly lower amount of oxidation (~80 % Ag + ). Note that other experimental studies from Schinca et al [142] as well as Giorgetti et al [143] both report on the generation of Ag/Ag 2 O core-shell NPs based on extinction spectroscopy and application of Mie theory modeling.…”
Section: Surface Oxidization[b] [%]mentioning
confidence: 99%
“…Surface oxidization is common for metallic nanoparticles produced by PLAL, including nanoparticles of noble metals [90][91][92][93]. Sylvestre et al found that the Au nanoparticles produced by femtosecond laser ablation of Au target in distilled water were negatively charged, and proposed it was due to partial oxidation of the Au nanoparticle surface.…”
Section: Chemical Reactionsmentioning
confidence: 99%
“…They also conclude from UV-visible absorption spectra that Cu-Cu 2 O core-shell structures are also formed during the ablation process. Taking into account these reports about the appearance of cuprous oxide as well as previous work by the authors on Ag-Ag 2 O Nps, 18 it is pertinent to analyze the characteristics of optical extinction spectra of small spherical assuming a possible core-shell CuCu 2 O Nps structure.…”
Section: Optical Extinction Calculationsmentioning
confidence: 99%
“…In this sense, optical extinction spectroscopy has demonstrated its ability to size core radius and shell thickness of noble metal Nps through the fitting of the full UV-Vis extinction spectra using Mie's theory 14 together with a conveniently modified metal bulk complex dielectric function that includes the size correction of free and bound electrons contributions. [15][16][17][18][19] During the last years, there has been a lot of research about Cu-Cu oxide nanocomposites [20][21][22][23][24][25][26][27][28] covering different aspects such as fabrication methods, optical properties, and structural analyses. From a general point of view, it can be said that knowledge of the mechanisms responsible for the formation of Cu-Cu oxide Nps is far from complete and may vary with the different conditions under which they were fabricated.…”
Section: Introductionmentioning
confidence: 99%